Exploring the Benefits and Challenges of Using Video-recorded Presentations in Group Settings - Nguyen, Thu Trang (South Sulawesi Education Development, 2025)
Presenting is an important aspect of the students’ academic experience in many teriary institutions in Vietnam. Many modules at higher education use oral presentations as a form of assessment and require students to verbally engage in small and large group settings to enhance learning. Thanks to technological developments, presentations can be given both directly in class and through online flatforms. The aims of this research were to gather the students’ insight into delivering group presentations through video recording. A qualitative survey was completed by 82 English-majored students from Faculty of Legal Foreign Languages, Hanoi Law University. All participants have completed their presentation skill course and were asked to write reflections at the end of the course. Based on students’ written feedback, thematic analysis was done to identify the benefits of recorded presentations as perceived by students and the difficulties faced by presenters in producing a video presentation. The results of this survey reveal that although there might be some challenges regarding video-making skill and lack of real audience, video-recorded presentations are advantageous for students as they boost motivation for learning, improve language skills, and help develop job-related competencies. From the findings of the research, some practical recommendations are made for language educators in similar contexts looking to integrate video technology into their teaching practices.